Nonperturbative aspects of the two-dimensional massive gauged Thirring model - Bufalo, R. [UNESP]; Pimentel, B. M. [UNESP] (World Scientific Publ Co Pte Ltd, 2014)
In this paper, we present a study based on the use of functional techniques on the issue of insertions of massive fermionic fields in the two-dimensional massless gauged Thirring model. As it will be shown, the fermionic mass contributes to the Green's functions in a surprisingly simple way, leaving therefore the original nonperturbative nature of the massless results still intact in the massive theory. Also, by means of complementarity, we present a second discussion of the massive model, now at its bosonic representation.
Keywords: Nonperturbative methods; mass insertion; path-integral bosonization